Análise de parâmetros espermáticos e fertilidade de ratos Wistar expostos ao interferon alfa - Rosa, Josiane de Lima [UNESP] (2014)
Interferons (IFNs) are small proteins known their antiproliferative and immunoregulatory activities and their crucial involvement in the cellular antiviral. Type I IFNs include the IFN-α, β e ω and are used therapeutically in the treatment of several kinds of cancers and hepatitis B and C. Endocrine dysfunction is among the adverse side effects of IFN-α. Little is know about the effects of IFNs on reproduction. Therefore, the present study aimed to investigated, in adult rats, the effects of subchronic exposure to different doses of IFN-α on male reproductive parameters. In the experiment 1, adult male Wistar rats (90 days/350-470g) were distributed in three experimental groups (n=10), one control, which received the vehicle, and two treated, subcutaneously, with 5x104 units/Kg e 10x104 units/Kg of IFN-α, diluted in saline. After 30 days of treatment the animals were weighed and euthanized for collection of reproductive organs. Right testis and epididymis, ventral prostate and seminal gland (without coagulating gland) of each animal were removed and weighed. Right testis and epididymis were used for the determination of sperm number and left epididymis for collection of sperm to evaluate of sperm motility and morphology and for intrauterine artificial insemination. The serum testosterone levels were also measured. In the experiment 2, another lot of animals, following the same experimental design, were used for collection of left testis and epididymis for to histopathological and morphometric evaluation. The body and reproductive organ weights were unchanged, as well as the daily sperm production, sperm transit time through the epididymis, sperm motility and morphology and fertility potential of animals. The histopathological and morphometric evaluation did not reveal injuries related to treatment. Thus, our results show that subchronic exposure to IFN-α did not interfere with levels of serum testosterone ...